Increased inflammatory markers with altered antioxidant status persist after clinical recovery from severe sepsis: a correlation with low HDL cholesterol and albumin - Vavrova, Lucie; Rychlikova, Jana; Mrackova, Magdalena; Novakova, Olga; Zak, Ales; Novak, Frantisek (Clinical and experimental medicine, 2016)
Markers of oxidative stress and antioxidant status in relation to inflammatory mediators in septic patients (SPs) during the course of sepsis and after recovery were analysed. Patients were 30 critically ill adults in severe sepsis/septic shock, 19 of which completed 3 samplings (S1: within 24 h after onset of sepsis, S7: 7 days after S1, R7: 7 days after clinical recovery). Comparing SPs with healthy controls (HCs), enhanced C-reactive protein, procalcitonin, bilirubin and CuZn-superoxide dismutase activity were found at S1 only. Oxidized low-density lipoprotein, conjugated dienes and nitrotyrosine were increased at S1, culminated at S7 and reverted nearly to HC levels at R7. Reduced catalase activity and serum amyloid were observed at S1 and endured until R7. Increase in IL-6, IL-10 and tumour necrosis factor alpha (TNF-α) with accompanying decrease in apolipoprotein A1, high-density lipoprotein (HDL) cholesterol, selenium, zinc, albumin, paraoxonase 1 and glutathione peroxidase 1 activity appeared at S1 and persisted until R7. TNF-α, IL-10 and markers of oxidative stress were in negative correlation with HDL cholesterol and albumin at R7. After clinical recovery, increased cytokines and decreased antioxidants were accompanied by lower albumin and HDL cholesterol levels. During this important and beneficial period of tissue repair, patients with prolonged persistence of this status are probably more vulnerable to secondary infections and should be dealt with as constituting a high-risk population.
Keywords: senioři; Sepsis; cytokiny; sérový albumin; Middle Aged; mužské pohlaví; Oxidative Stress; Prospective Studies; Cytokines; Antioxidant enzymes; Albumin; Serum Albumin; ženské pohlaví; Humans; prospektivní studie; Oxidative stress; sepse; lidé středního věku; HDL cholesterol; HDL-cholesterol; oxidační stres; Female; Aged; Cholesterol, HDL; lidé; Male